Land suitability assessment of soils for rubber and cashew cultivation in the Coastal Area of Bodo City, Rivers State, Southern Nigeria - Kaananwii Dum Peter; Lesi Dike Gbaraneh (Jurnal Ilmu Pertanian, 2021)
The research was carried out in Bodo city in Gokana Local Government of Rivers State, Southern Nigeria to evaluate the land suitability for rubber and cashew cultivation using the relevant land suitability guidelines for the cultivation of the two cash crops of interest. Mapping of the 100 ha of land in Bodo city was done using the rigid grid method of soil survey. The three mapping units (summit, middle slope and valley bottom) were identified and delineated. Three representative soil pedons of 2 m x 2 m x 2 m were dug and described by horizon from top to bottom (0 cm to 200 cm). Soil samples were collected from identifiable horizons and processed for laboratory analysis using standard routine laboratory methods most appropriate. The results showed that pedons 1 and 3 covering 86,000 ha of the entire study area were found to be moderately suitable for rubber cultivation with limitation in soil physical characteristics (texture) and fertility (low base saturation < 50 %). Pedon 2 covering 14,000 ha of the total land of the study area was marginally suitable due to limitation in soil fertility (low base saturation < 80 %). Pedon 1, 2, and 3 were also moderately suitable for cashew cultivation in the study area with limitation in soil physical characteristics (texture) and fertility (low organic carbon), while limitation in wetness (poor drainage) was peculiar to pedon 3 only. Thus, soils in the study area were moderately suitable for both rubber and cashew cultivation in the area.